THE IMPLEMENTATION OF ARTICLE 31 PARAGRAPH (1) OF THE 1945 CONSTITUTION IN FULFILLING THE RIGHT TO EDUCATION FOR WOMEN IN TANJUNGSARI VILLAGE - Fitriah, Robiatul; Nugraha, Yogi; Saylendra, Nadya Putri (Institut Pendidikan Indonesia, 2025)
Abstract Article 31 paragraph 1 of the 1945 Constitution states that every citizen has the right to education. However, in reality, not all girls have received their right to education fairly, especially in rural areas. Therefore, the purpose of this study is to examine the implementation of Article 31 Paragraph (1) of the 1945 Constitution in fulfilling girls' right to education in Tanjungsari Village, Cilebar District, Karawang Regency. Using a qualitative descriptive approach through interview and observation techniques, this study involved 5 girls who had dropped out of school, 5 of their parents, and 1 village head as informants. The results show that although much infrastructure is available, the fulfillment of the right to education is not optimal. Of the 52 children who dropped out of school in 2023, 34 of them were girls. Economic factors are the main obstacle (limited costs), exacerbated by a patriarchal culture that considers higher education unimportant for women. The implementation of constitutional norms has not been optimal due to the absence of a systematic cooperation program between the village government and schools and the lack of structured socialization. These findings indicate the need for real intervention by the government, village officials, and families to ensure the fulfillment of girls' educational rights comprehensively and equally in accordance with the constitutional mandate. Keywords: Implementation of the constitution, right to education, girls, gender gap, village government